POLITE STRATEGIES IN INTERVIEW VIDEOS OF Asian Boss AND Bondo Wani - Purwitarini, Dhyan (Jurnal Pena Indonesia, 2020)
The research analyzed the use of positive and negative politeness strategies in the Interview videos of ASIAN BOSS and BONDO WANI. Both of these videos discuss about the sensitive topic in Indonesia. This research applies descriptive qualitative method. Then, the utterances in these two videos transcribed and analyzed descriptively by politeness theory of Brown and Levinson (1978). The data taken contain positive and negative politeness strategies. In collecting the data, the researcher applies some steps: watching the interview videos for several times, taking note the conversation, and observes the conversation that highly applies positive and negative politeness strategies within the interview. The results of the study showed that BONDO WANI with the host is Dono Pradana and the people from Surabaya as the hearer used positive politeness strategies more than ASIAN BOSS and ASIAN BOSS with the interviewer and the interviwees are from Jakarta used negative politeness strategies than BONDO WANI based on Brown and Levinson (1978) theory. There were 107 utterances that can be categorized as negative politeness and positive politeness strategy. There are 37 data from negative politeness that showed by both ASIAN BOSS and BONDO WANI and 70 data from positive politeness strategies applied based on ASIAN BOSS and BONDO WANI. This research is expected can be beneficial to people who intend to understand particularly that even In Indonesia has various tribes with various languages in it.